2016
DOI: 10.1007/s11010-015-2652-3
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic acid phenethyl ester activates pro-apoptotic and epithelial–mesenchymal transition-related genes in ovarian cancer cells A2780 and A2780cis

Abstract: Ovarian cancer is a highly aggressive pathology, displaying a poor prognosis and chemoresistance to classical therapy. The present study was conducted to evaluate the effect of caffeic acid phenethyl ester (CAPE) on survival of ovarian cancer cell lines, A2780 (sensitive to cisplatin) and A2780cis (resistant to cisplatin). MTT assay was used to evaluate cell viability, while the apoptotic processes were examined by flow cytometry and qRT-PCR. A reduction of cell proliferation and activation of the apoptosis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 34 publications
3
16
0
Order By: Relevance
“…Furthermore, p53 can influence apoptosis by regulating Bcl-2 (33). Previous studies have revealed that >50% of tumors are associated with p53 gene mutation; wild-type p53 gene therapy has been suggested to strengthen sensitivity to cisplatin in SKOV3 cells (34)(35)(36). In the present study, it was demonstrated that salidroside has the ability to induce OC apoptosis.…”
Section: Discussionsupporting
confidence: 51%
“…Furthermore, p53 can influence apoptosis by regulating Bcl-2 (33). Previous studies have revealed that >50% of tumors are associated with p53 gene mutation; wild-type p53 gene therapy has been suggested to strengthen sensitivity to cisplatin in SKOV3 cells (34)(35)(36). In the present study, it was demonstrated that salidroside has the ability to induce OC apoptosis.…”
Section: Discussionsupporting
confidence: 51%
“…Namely, it is well recognized that both caffeic and gallic acid, that are present in EA extract, possess strong anti-proliferative and cytotoxic properties in wide range of tumor types such as those used in this study (breast, cervical, ovarian, prostate carcinoma). [51][52][53] These phenolic acids affected main signaling pathways involved in cell cycle progression and cell death. Moreover, they interfered with migrative and invasive properties, epithelial/ mesenchimal transition and even angiogenesis.…”
Section: Enzyme Inhibitory Effects Of the A Vulgaris Extractsmentioning
confidence: 99%
“…CAPE has multiple biologic active properties among which we can list: antiviral, antibacterial, antioxidant, anti-inflammatory and overall anti-cancer activities [68,69,70]. CAPE is targeting the NFκB transcription factor, promoting apoptosis in a wide range of cell lines [71,72,73,74]. For example, HL-60 cells of human leukemia subjected to the CAPE treatment revealed increased apoptosis by activation of different regulatory elements caspase-3 and BAX regulator and suppression Bcl-2 [69].…”
Section: Phytochemical Compounds and Cancermentioning
confidence: 99%
“…CAPE was demonstrated to act as a biomarker with active role in chemoprevention and chemotherapy in oral cancer patients inhibiting Akt signalling, cell cycle regulatory proteins and NFκB function [78,79]. It has been demonstrated that CAPE has potential application in cervical cancer [80] or ovarian cancer also [74]. …”
Section: Phytochemical Compounds and Cancermentioning
confidence: 99%